2019
DOI: 10.1210/jc.2018-01491
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Incident Dementia According to Metabolic Health and Obesity Status in Late Life: A Population-Based Cohort Study

Abstract: Advance Articles are PDF versions of manuscripts that have been peer reviewed and accepted but not yet copyedited. The manuscripts are published online as soon as possible after acceptance and before the copyedited, typeset articles are published. They are posted "as is" (i.e., as submitted by the authors at the modification stage), and do not reflect editorial changes. No corrections/changes to the PDF manuscripts are accepted. Accordingly, there likely will be differences between the Advance Article manuscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 61 publications
4
34
1
2
Order By: Relevance
“…Moreover, growing body of studies suggested that overweight in older age may be a protective factor for AD. Overweight older adults had a lower incidence or a later onset of AD than those of normal weight or low weight [33][34][35]. Our results indicated that the protective effect of plasma ApoB on CSF AD core biomarkers may be the potential mechanism.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, growing body of studies suggested that overweight in older age may be a protective factor for AD. Overweight older adults had a lower incidence or a later onset of AD than those of normal weight or low weight [33][34][35]. Our results indicated that the protective effect of plasma ApoB on CSF AD core biomarkers may be the potential mechanism.…”
Section: Discussionmentioning
confidence: 64%
“…Overweight older adults, especially metabolic health individuals that were similar to the participants in our study, had a lower incidence or a later onset of AD than those of normal weight or low weight. [35][36][37] Our results indicated that the protective effect of serum ApoB on CSF AD core biomarkers may be the potential mechanism. In other words, the serum ApoB's potential ability to alleviate early pathological changes may contribute to slow the progression of the disease in overweight older adults, but not in normal weight older adults.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, growing body of studies suggested that overweight in older age may be a protective factor for AD. Overweight older adults had a lower incidence or a later onset of AD than those of normal weight or low weight (36)(37)(38).…”
Section: Discussionmentioning
confidence: 89%